Sustainable environmental protection from pollution: A comparative study between Islamic Sharia and international law - Al-Haqshah, Faihan Farraj (Research Journal in Advanced Humanities, 2026)
This paper explores the issue of pollution as a source of environmental pollution that can be tackled by the Islamic Sharia and the international law by a comparative framework of sustainable environmental protection challenges in air, water, soil, biodiversity, human health, and intergenerational equity in view of the increasing environmental problems threatening our environment. Although over an advanced system of international environmental regime has been developed based on some vital principles like precautionary principle, polluter pays principle and intergenerational equity, combined with the principle of common, but differentiated responsibilities, the prevalent gaps in implementation and the weak enforcement mechanisms have remained as tactics of negating its overall effectiveness. Conversely, the study previews the normative basis of Islamic Sharia in governing human-environment relations which is anchored on the notion of khilafah (stewardship), amanah (trust), and mizan (balance), and the ban on fasad (environmental corruption). It shows that environmental protection is natural continuation of higher goals of Sharia (maqasid al-sharia) especially the protection of life, generation, and property. The maxims of the foundation of Islamic law like no harm and no reciprocating harm, and harm must be removed offer an excellent normative grounding of an environmental accountability that portrays a significant conceptual consistency with the modern international environmental law. Based on a comparative-synthetic approach, the research constructs a multi-level integrative model between Sharia values and international law by inclusivity in normative underpinnings, that genes equalization environmental governance in Muslim acquired countries and can also play a role in global discussions about sustainability and environmental justice.